Globalization Approaches to Diversity - Cuadra-Montiel, Hector (IntechOpen, 2012)
The book Globalization - Approaches to Diversity takes the ambitious undertaking of presenting a series of global issues that range from historic to contemporary, from transnational to local, and from cultural to institutional. It consists of twelve chapters divided into three sections: Globalization Agendas, Globalization Policies, Globalization Experiences. Its authors embody a global research culture. One that is plural, growing and dynamic, as it is evidenced in their respective agendas and methodological approaches. The value of this book lies in its diversity, and its merit will be appreciated by a global community of scholars.